Legal Foundations and Comparative Analysis of Early Childhood Education Practices in The Turkish World - KOL, Suat; TUNÇELİ, Hilal İlknur (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
Early childhood education is a very important period for the education and development of the child. Many critical stages in the mental, physical and spiritual development of the child take place in this period. In addition, the gains to be obtained in this period form the basis of the child's education and academic development. Today, while the prevalence of early childhood education is close to 100% in many developed countries, this is not at the desired level in the countries that make up the Turkish World. The aim of this study is to examine the early childhood education in a comprehensive manner in independent Turkish states. In this context, as working group; Azerbaijan, Kazakhstan, Kyrgyzstan, Cyprus, Turkey, and Uzbekistan's document analysis related to early childhood education was carried out adhering to the title specified in the data collection tool. Historical analysis, one of the qualitative research methods, was used in the study. According to the data obtained; The prevalence ratio of pre-school education is the most in Turkey with 45.4%, and the least in Uzbekistan with 23.8%. It is seen that while the start of early childhood education in Turkish Republic of Northern Cyprus (TRNC) and Turkey dates back to primary school, it begins in the early 1900s in other countries. Age classification varies in every country and the education is carried out through this classification in the early childhood education institutions. When the teacher training programs are considered, the teaching profession is acquired through undergraduate education in all countries. However, the right to teach is given in 2-4 years in Azerbaijan, 3-5 years in Kyrgyzstan and in 4 years and 4+1 supplementary training in Kazakhstan, TRNC and Turkey.